2015
DOI: 10.1111/acer.12843
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Exposure is Associated with Decreased Neurogenesis, Aberrant Integration of Newborn Neurons, and Cognitive Dysfunction in Female Mice

Abstract: Background Neurological deficits of alcohol use disorder (AUD) have been attributed to dysfunctions of specific brain structures. Studies of alcoholic patients and chronic alcohol exposure animal models consistently identify reduced hippocampal mass and cogntive dysfunctions as a key alcohol-induced brain adaptation. However, the precise substrate of chronic alcohol exposure that leads to structural and functional impairments of the hippocampus is largely unknown. Methods Using a calorie-matched alcohol feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…At the cellular level, acute or chronic administration of drugs with addictive potential modifies hippocampal-dependent LTP (Kutlu and Gould, 2016;LĂŒscher and Malenka, 2011). Additionally, opioids, psychostimulants, and alcohol interfere with neurogenesis in the adult hippocampus (Eisch and Harburg, 2006;Golub et al, 2015), which may affect normal functioning.…”
Section: Hippocampus-dependent Learningmentioning
confidence: 99%
“…At the cellular level, acute or chronic administration of drugs with addictive potential modifies hippocampal-dependent LTP (Kutlu and Gould, 2016;LĂŒscher and Malenka, 2011). Additionally, opioids, psychostimulants, and alcohol interfere with neurogenesis in the adult hippocampus (Eisch and Harburg, 2006;Golub et al, 2015), which may affect normal functioning.…”
Section: Hippocampus-dependent Learningmentioning
confidence: 99%
“…AW increases the spine density of newborn DGCs. Our previous study showed that chronic alcohol exposure disrupted the synaptic connectivity of hippocampal newborn DGCs, dramatically reducing the density of dendritic spines of newborn DGCs (27). Here, we examined whether AW induces structural plasticity and impacts the function of newborn DGCs during a protracted abstinence.…”
Section: Resultsmentioning
confidence: 93%
“…As a result, both control and alcohol-fed mice consumed the same amount of calories during the experimental period (ref. 27 and Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.128770DS1). During the 4-week alcohol feeding period, mice consumed alcohol daily (20.2 ± 1.53 g/kg/day) and accumulated a significant amount of alcohol (545.0 ± 1.53 g/kg) (Supplemental Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive literature has established that repeated administration of drugs of abuse, such as alcohol [52][53][54][55] , cocaine [56][57][58][59] , and opiates [60][61][62] , decreases adult hippocampal neurogenesis, as reviewed elsewhere [63][64][65] . However, therapeutic doses of amphetamines increase neurogenesis in at least one mouse model [66] .…”
Section: Drugs Of Abusementioning
confidence: 99%